Rudolf Steiner and Contemporary Art - Assmann, Aleida; Boehm, Gottfried; Breidbach, Olaf; Brock, Bazon; Brüderlin, Markus; Gotz, Werner; Groos, Ulrike; Kugler, Walter; Loers, Veit; Meyer-Dohm, Peter; Müller-Pietralla, Wolfgang; Schily, Konrad; et al. (Wolfsburg : Kunstmuseum Wolfsburg, 2010)
Steiner, Rudolf ; Merz, Mario ; Beuys, Joseph ; Penone, Giuseppe ; Kapoor, Anish ; Federle, Helmut ; Cragg, Tony Anthony ; Eliasson, Olafur ; Finch, Spencer ; Grosse, Katharina ; Nicolai, Carsten ; Albers, Jan ; Angioletti, Meris ; Lindena, Kalin ; Dybbroe Moller, Simon ; Wieser, Claudia ; Graf, Manuel ; Ribbeck, Bernd
Rudolf Steiner and Contemporary Art, Kunstmuseum Stuttgart, Stuttgart, 2010-05-13. 2011-02-05 / Wolfsburg Kunstmuseum, Wolfsburg, 2010-10-03. 2011-05-22
boek